(untitled) (Journal of human and social sciences, 2025)
The role of colleges of education in preparing basic education teachers depends on the strategic plans for education. These plans and strategies include providing educational and development programs aimed at preparing the teacher and qualifying him optimally, which is considered the focus of the educational process in colleges of education. By developing appropriate plans, mechanisms, and a studied strategy for the educational and pedagogical process, The goals and objectives of these educational institutions are achieved, and the ultimate goal of the outcomes of colleges of education is achieved in providing competent and effective teachers at all educational levels, and positively affects the quality of performance, especially in the basic education stage. Hence the aim of the study came, which is to answer the main question: What is the relationship between Strategies of colleges of education and teacher preparation in the basic education stage? It is divided into sub-questions about strategies in educational aspects, pedagogical aspects, and aspects of practical field applications. This study comes in three parts: the first: deals with the general framework and methodology, the second deals with the conceptual theoretical framework for the role of colleges of education in preparing teachers in the basic education stage from a strategic perspective, and the third deals with The practical field and statistical aspect of the data and a conclusion with the results and recommendations.